Equity and COVID-19 treatment allocation: A questionable criterion - Vogelstein, Eric (Bioethics, 2023)
Since the onset of the COVID-19 pandemic, a controversial criterion for allocating scarce medical treatment has been defended and incorporated into policy: the criterion of equity. Equity-included allocation schemes prioritize, to some degree, patients from marginalized or historically disadvantaged racial/ethnic groups, or patients with low socioeconomic status, for scarce treatment. The use of such criteria has been most prominently defended in two ways: (1) as reflecting a risk factor for severe COVID-19, and thus as a way of tracking medical need, and (2) as a form of remedial justice, viz. a way of redressing disparities in COVID outcomes that are caused by underlying unjust social conditions. Here, we delineate and critique those arguments. We argue that not only are such arguments unconvincing but also that there are compelling moral reasons to reject the sort of equity-included allocation schemes at issue.